Ornamental plants in Chapecó: market characteristics and opportunities for family farms - Spier, Juliane; Silva, Vanessa Neumann; Dal Belo Leite, João Guilherme (Ornamental Horticulture, 2020)
Floriculture is very lucrative to small producers as it requires small land areas, with usually short production cycles. The region of Santa Catarina West in Brazil has growth potential in the cultivation of ornamental plants, although it is not practically observed, as the productive chain of this sector has little or no organization, making it imperative to study the causes of this problem. Therefore, the aim of this study was to characterize the productive chain, market, and commercialization of ornamental plants in Chapecó-SC. The proposed study was carried out in an integrated manner in Chapecó-SC, through structured interviews with farmers, traders, and consumers of flowers and ornamental plants. The study sample consisted of 45 consumers, 24 producers, and 18 commercial establishments. Only three producers of ornamental plants in Chapecó were identified among the participants interviewed, although 84% believed that the municipality has demand for floriculture products, and only 21% of the interviewees have thought about cultivating ornamental plants. The market and commercialization of flowers and ornamental plants in Chapecó are dependent highly on the supply of products from the state of São Paulo, especially form the region of Holambra. The commercialization is predominantly in supermarket chains, for ease of access to consumers. The primary factor affecting the commercialization of ornamental plants is the price, because a dearth of producers in the region leads to an increase in the price, especially due to the long transportation.